Electrical properties of pure NiO and NiO:Au thin films prepared by using pulsed laser deposition - Jamal, Raied K. (Iraqi Journal of Physics, 2019)
The electrical properties of pure NiO and NiO:Au Films which are deposited on glass substrate with various dopant concentrations (1wt.%, 2wt%, 3wt.% and 4wt.%) at room temperature 450 Co annealing temperature will be presented. The results of the hall effect showed that all the films were p-type. The Hall mobility decreases while both carrier concentration and conductivity increases with the increasing of annealing temperatures and doping percentage, Thus, indicating the behavior of semiconductor, and also the D.C conductivity from which the activation energy decrease with the doping concentration increase and transport mechanism of the charge carriers can be estimated.